MODEL PEMANFAATAN ATAS TANAH TERLANTAR DARI HAK GUNA USAHA DIKAITKAN DENGAN PENGEMBANGAN USAHA PONDOK PESANTREN DI KAWASAN BOPUNJUR - Rizal Syamsul Maarif; Martin Roestamy (JURNAL ILMIAH LIVING LAW, 2021)
The objectives of this study are 1) To identify and analyze the concept and politics of enclaving abandoned land ex-land use rights (HGU) in Indonesia 2) To find out and conduct legal analysis regarding the development of an enclaving model of abandoned land ex-land use rights (HGU) of PTPN VIII for the development of a Pondok Pesantren business in the Bopunjur area. The research method used in this research is normative juridical analysis research with a qualitative approach combining secondary legal materials with primary legal materials so as to produce a fact analysis that occurs in the field. The results of this study are: 1) the concept and politics of enclaving on ex-plantation and agricultural land in the Bopunjur area can be utilized as a business development for a Pondok Pesantren, taking into account the 3-year period the land is not suitable for its purpose. And even tend to be neglected or have experienced several cultivated operations. 2) an enclaving development model for abandoned PTPN VIII land, namely by following the asset empowerment cooperation procedure for 5 years, on the way it can be upgraded to a right of use certificate and for 3 consecutive years you can request enclav to the Provincial BPN because Bopunjur is a direct area under the auspices of the Provincial BPN by observing the principle of benefiting the abandoned land into productive activitiesKeywords : Enclaving Model Development, Utilization Principles, Abandoned Land